Sources of Timber and Constraints to the Timber Acquisition of Jepara‘s Small-Scale Furniture Industries - Efi Yuliati Yovi; Bahruni .; Dodik Ridho Nurrochmat (Institut Pertanian Bogor (IPB University), 2009)
Teak and mahogany furniture industries in Jepara are dominated by small-scale industrial unit, produce simple type of furniture mostly made from less than 28 cm diameter of teak log. Timber main producers of the industries are Perum Perhutani and village plantations. Small-scale furniture industries characterized by limited capital, therefore there is no log stocking behavior. This resulted in a close interaction on log supply and demand dynamics between both traders and industries. As a consequence of drastic increase in the number of the industries, one big question on sustainability of raw material for the industries has been emerged. Data taken from this research indicated scarcity of teak and mahogany log. Limited capital directs industries to blame the difficulties mainly due to increasing timber price. Additionally, the industries (and log traders) who are stand mostly in level 2 of log distribution chain mentioned that compared to 10 years ago, there is difficulty in obtaining bigger log diameter. It is a very interesting finding that the industries do not certainly sense timber scarcity as one possibility reason behind the timber scarcity. As weakness on business resilience has been the main characteristic of the industries, the threads would give a direct impact to the industries soon or later. To this, serious efforts in maintaining timber sustainability, shortening timber distribution chain, together with capital strengthening seem to be the fastest way in supporting the sustainability of the industries.Keywords: teak furniture, timber price, small-scale, timber scarcity